Fondaparinux for the prevention or treatment of venous thromboembolism related to lower limb trauma: evidence today. - Nikolaos K. Kanakaris; Nikolaou, Vassilios S; Tosounidis, Theodoros; Giannoudis, Peter V (Curr Vasc Pharmacol, 2008)
Patients with lower limb and pelvic trauma, or undergoing major orthopaedic surgery represent one of the highest risk groups for the development of venous thromboembolism (VTE). A significant number of pharmacological and mechanical agents have been used for the prophylaxis and treatment of VTE. Fondaparinux is a relative new pharmacological agent that selectively binds to antithrombin, and represents a new class of synthetic selective inhibitors of activated factor X. Eleven percent of the fondaparinux-related English language literature, between 2001 and 2007, refers to orthopaedic trauma, and was the sample assessed for this critical analysis review. The clinical studies evaluating the safety, efficacy, and financial implications associated with lower limb orthopaedic trauma show that fondaparinux has comparable results with the well-established use of enoxaparin. However, the scientific community has raised several issues regarding mostly fondaparinux's safety, timing of its 1(st) dose, bleeding side effects, duration of administration and lack of a reliable reversing agent. Further trials are necessary focusing on the safety and efficacy of this drug mostly in relation to clinical relevant outcomes and to different fields of trauma surgery (pelvis, long bone fractures and polytrauma patients).
Keywords: Anticoagulants; Fondaparinux; Humans; Lower Extremity; Orthopedic Procedures; Pelvis; Polysaccharides; Venous Thromboembolism